Thermal conductivity of silicone elastomer with a porous alumina continuum - Song Qichao (De Gruyter, 2021)
PAC provided numerous interpenetrated channels for the access of SR and prompted the formation of interconnected three-dimensional networks for remarkable improvement on the thermal conductivity of PAC/SR composites.